METHOD AND APPARATUS FOR PROCESSING OPERATION, ADMINISTRATION AND MAINTENANCE OAM MESSAGES - ZHAO, Yuhai (2016)
Provided in the present invention are a method and apparatus for processing operation, administration and maintenance OAM messages. The method comprises: acquiring an OAM message from a network side; determining whether the OAM message is a non-home line card OAM; and sending the OAM message to a switching network when determining that the OAM message is the non-home line card OAM. With the present invention, the problem of large cache overhead in line card OAM queues in related techniques is solved, and further the effect of lowering the cache overhead in line card OAM queues is achieved. L'invention concerne un procédé et un appareil de traitement de messages d'opération, d'administration et de maintenance (OAM). Le procédé comprend : l'acquisition d'un message OAM depuis un côté réseau ; la détermination du fait que le message OAM est ou non un OAM de carte de ligne non domestique ; et l'envoi du message OAM à un réseau de commutation lorsqu'il est déterminé que le message OAM est l'OAM de carte de ligne n